Social Skills and Psychological Disorders: Converging and Criterion-Related Validity for YSR and IHSA-Del-Prette in Adolescents at Risk - Del Prette, Zilda Aparecida Pereira; Universidade Federal de São Carlos (2011)
This study evaluated indexes of converging and criterion-related validity for the Social Skills Inventory for Adolescents (IHSA-Del-Prette) and the Youth Self-Report (YSR) in two samples: one referring to clinical service (CLIN), with 28 adolescents (64.3% boys), 11 through 17 years old (M = 13.75; SD = 1.74), and the other referring to a psycho-educational program (PME = 46.2%), mainly composed of boys (91.7%) aged 13 through 17 (M = 15.33; SD = 1.47). Both samples completed the two inventories. Results showed a high incidence of psychological disorders in both samples (between 4% and 79% in the borderline or clinical range on YSR scales) and accentuated deficits in the general and subscale scores of IHSA-Del-Prette, especially on the frequency scale (25% to 58%). The correlations between the instruments in the two groups supported criterion-related and converging validity. Some issues concerning the differences between the samples and about the construct of social competence, underlying these inventories, are discussed